1983
DOI: 10.1002/1097-0142(19830815)52:4<737::aid-cncr2820520428>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of pleural effusions in patients with breast cancer a randomized trial

Abstract: In a controlled randomized trial, 46 patients with pleural effusions secondary to breast cancer were treated at first diagnosis with either intracavitary mustine or talc, to determine which agent produced the more effective pleurodesis. Of the 37 evaluable patients, control of the effusion was achieved in 9/17 (56%) of those treated with mustine and 18/20 (90%) of the talc group (P > 0.025). This suggests that early treatment with intracavitary talc can effectively palliate this complication of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 8 publications
0
29
0
4
Order By: Relevance
“…The response rate to ST for breast cancer is midway between that for small cell lung cancer and nonsmall cell lung cancer. Some studies have reported that control of pleural effusion was not significantly different between ST and P-ST [5][6][7]. Based on these studies, breast cancer patients with MPE are currently administered ST as the first choice for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate to ST for breast cancer is midway between that for small cell lung cancer and nonsmall cell lung cancer. Some studies have reported that control of pleural effusion was not significantly different between ST and P-ST [5][6][7]. Based on these studies, breast cancer patients with MPE are currently administered ST as the first choice for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines are based on retrospective studies conducted in the 1970s and 1980s that reported that the control of pleural effusion did not significantly differ among local, systemic and combined therapies [5][6][7]. Systemic therapy (ST) has traditionally been the mainstay of treatment for metastatic breast cancer with or without pleurodesis.…”
mentioning
confidence: 99%
“…Furthermore, successful pleurodesis is less likely if the pleural malignancy is advanced. Therefore, some clinicians advocate that pleurodesis be attempted sooner rather than later during the course of the disease [3,4]. We currently agree with this position, in order to avoid attempting pleural symphysis when the effusion is rapidly recurrent and the general condition of the patient has deteriorated.…”
Section: Is the Effusion Recurrent?mentioning
confidence: 98%
“…Pleural metastases are common in the course of breast cancer, affecting 10-50% of breast cancer patients [1][2][3]. This pleural involvement may be the first and only manifestation of recurrent disease in 20-40% of these patients [1,2,4].…”
mentioning
confidence: 99%